Kekerasan Dalam Pendidikan Sebuah Survei atas Praktek Pendidikan di Flores NTT - Adi, Rianto (Jurnal Etika Respons, 2009)
Violence is a real fact that can be described into many forms: physical, emotional, sexual. This article describes the way the people of Flores think about it and justify it into educational action. The survey considers that although violence can be tolerated, the people of Flores implicitly refused violence for the sake of their future generation.